Resting Respiratory Sinus Arrhythmia in Suicide Attempters - Tsypes, Aliona (Psychophysiology, 2017)
Although suicide attempts (SA) occur across a broad range of diagnoses as well as in the absence of a diagnosable disorder, most studies to date have focused on them within a single, specific disorder. Consistent with the NIMH RDoC initiative to identify biobehavioral vulnerabilities that cut across diagnoses, the goal of the present study was to examine potential differences in resting respiratory sinus arrhythmia (RSA) levels in a large, diagnostically heterogeneous sample of women with and without a history of SA who were matched on a broad range of demographic and clinical variables. Participants were 112 women with (n=56) and without (n=56) a history of SA recruited from the community. The two groups were equated on approximate age, race, household income, and lifetime histories of psychiatric diagnoses. Resting electrocardiogram was recorded during a 2-minute long rest period. RSA was calculated via spectral power analyses with a fast Fourier transformation. We found that women with a history of SA exhibited significantly lower resting RSA levels than women with no history of SA, and this difference was maintained even after statistically controlling for the potential influence of women’s history of psychiatric diagnoses and their current symptoms of depression and anxiety. These findings suggest the presence of a link between resting RSA and SA history.